Chitosan derivatives, composites and applications - Ahmed, Shakeel 1989-; Ikram, Saiqa (Wiley, 2017)
This book delves deeply in to the preparation, characterization and multiple applications of chitin and chitosan. The 17 chapters written by leading experts is an excellent reference source and state-of-the-art review for researchers and scientists using chitosan or biopolymers in their respective areas. This book is divided into following sections:- Production and derivatives of chitosan- Chitosan in the textile and food industries- Chitosan in biomedical applications- Chitosan in agriculture and water treatment The book is practical as readers will be able to see descriptions of chitosan production methods as well as techniques that can be used to estimate and modify their physical and chemical properties. It provides a full description not only of the traditional and recent developments in the applications of chitosan in the fields of biotechnology, environmental studies, food, medicine, water treatments, drug delivery, but it includes all of the therapeutically usages as well
Includes bibliographical references and index
Keywords: Chitosan / fast / (OCoLC)fst00858000; Chitosan / Biotechnology / fast / (OCoLC)fst00858001; SCIENCE / Chemistry / Industrial & Technical / bisacsh; TECHNOLOGY & ENGINEERING / Chemical & Biochemical / bisacsh; Chitosan / Biotechnology; Chitosan / Industrial applications